Ε-Coverings of Hölder-Zygmund Type Spaces on Data-Defined Manifolds. (17th June 2014) - Ehler, Martin; Filbir, Frank
Abstract : We first determine the asymptotes of the ε -covering numbers of Hölder-Zygmund type spaces on data-defined manifolds. Secondly, a fully discrete and finite algorithmic scheme is developed providing explicit ε -coverings whose cardinality is asymptotically near the ε -covering number. Given an arbitrary Hölder-Zygmund type function, the nearby center of a ball in the ε -covering can also be computed in a discrete finite fashion.